Posicionamento e imagem de marca no mercado de café verde - Caldeira, Lúcio Garcia (2015)
It has been found with this study as the meanings were built for various green coffee types or brands in the international market. The meaning of the brand was the central theme of the work and after clarify three concepts related to the meaning: identity, positioning and brand image, left to understand the role of positioning strategies in the construction of the meaning of green coffee brands. Each of the types or brands studied cafes have an image in the international market. These images were the result of planned positioning strategies and other unplanned, but the fact is that their identities influenced the image or meaning they possess. Therefore, using secondary information, it found that coffee from Colombia built its planned form of positioning and is perceived as superior to coffee from Brazil. Other Milds coffee took advantage of the Colombian strategy and were perceived as inferior to the Colombian coffee and superior to Brazilian Coffees, which in turn is perceived as the lowest in the world arabica, which still puts him in a position of superiority over theRobusta group coffee. Specialty coffees, Certificates coffees and Coffes from Origin types planned their positions and are perceived as superior to traditional commodities. The CD is perceived as an intermediary between the milds and the natural coffees. Finally, the study also sought, based on the theoretical and analytical procedure developed to explain the meanings of brands or types of coffees, propose positioning strategies for Natural coffees from Brazil and from 100% Arabica coffee. In this sense, it argued that Brazil's Natural coffee needs to position itself as the ideal raw material for the expresso type coffees. "The best for expresso" would be the way to rescue the image of dried coffee with the peel - the typical coffee from Brazil. In the case of 100% Arabica, defended himself planning a position to educate the consumer of coffee in the sense of working-knowledge of the difference between a pure Arabica coffee and a blend of Arabic and robust. This, seeking the appreciation of Arabic. Finally, through this study, it was describe and analyze the positions and images of these brands or types of green coffee on the international market and to propose positioning strategies to interfere with the image of two types of coffees.